2019
DOI: 10.1002/asjc.2164
|View full text |Cite
|
Sign up to set email alerts
|

Social Optimal mean field control problem for population growth model

Abstract: In this paper, we consider a class of social optimal mean field control problem of the population growth model. Suppose a fishpond has N-fish schools, the population of each of them is described by a geometry Brownian motion, the fisherman is on one hand to minimize the total nourishment investments and on another hand to minimize the expected population level measured by the state average of the population of all fish schools. By solving an optimal control problem involved N-controls and approximating the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Good references of Asmussen and Hering [1], Athreya and Jagers [2], Athreya and Ney [3], Chen et al [4], Ezhov [5], Harris [6], Kalinkin [7], Li [8,9], Li and Wang [10], Sevast'yanov [11] considered kinds of generalized branching models. Whilst for more other recent excellent developments, we can see Chen et al [12,13], Li [14] and Yu et al [15][16][17], Ren et al [18], Xiong and Yang [19], Zhang [20], Zhang [21] and Zhang et al [22], and so on. In this paper, we consider a more challenging and practical meaning model, which involved m > 2 particles collision, and hence, investigating the properties of such model is of great significance.…”
Section: Definitionmentioning
confidence: 99%
“…Good references of Asmussen and Hering [1], Athreya and Jagers [2], Athreya and Ney [3], Chen et al [4], Ezhov [5], Harris [6], Kalinkin [7], Li [8,9], Li and Wang [10], Sevast'yanov [11] considered kinds of generalized branching models. Whilst for more other recent excellent developments, we can see Chen et al [12,13], Li [14] and Yu et al [15][16][17], Ren et al [18], Xiong and Yang [19], Zhang [20], Zhang [21] and Zhang et al [22], and so on. In this paper, we consider a more challenging and practical meaning model, which involved m > 2 particles collision, and hence, investigating the properties of such model is of great significance.…”
Section: Definitionmentioning
confidence: 99%
“…Yang and Deng [25] study the discounted Gerber-Shiu type function for a perturbed risk model with interest and periodic dividend strategy. Other recent articles on risk models with dividend strategy and capital injection involving periodic observations can be found in Zhang and Liu [26], Zhang [27], Zhang and Han [28], Zhao et al [29], Pérez and Yamazaki [30], Noba et al [31], Dong and Zhou [32], Xu et al [33], Zhang et al [34], Liu and Yu [35], Zhang and Cheung [36], Yu et al [37] and Liu and Zhang [38].…”
Section: Introductionmentioning
confidence: 99%
“…In [1], where the surplus dynamics followed a discrete time random walk, De Finetti showed that a barrier dividend strategy is the optimal dividend strategy because it produces the maximum firm value of the company. From then on, the optimality of the barrier dividend strategy has been proved for various risk models under suitable assumptions, see, for instance, Loeffen [3], Loeffen and Renaud [4], Yin and Wang [5], Yuen and Yin [6], Wang and Zhou [7], Yu et al [8], and the references therein.…”
Section: Introductionmentioning
confidence: 99%